Práticas fisioterapêuticas na acuidade visual - Tacca, Jandira (My University, 2019)
Introduction: In Ophthalmic Physiotherapy exercises are performed to increase ocular function. Myopia and Astigmatism are refractive errors that cause altered vision at a distance. Objective: this study aims to verify the influence of physical therapy on visual changes and on muscle pain and discomfort. Methodology: The research is characterized by a qualitative paradigm of descriptive observational type, type of study before and after with a group of five volunteers who presented Astigmatism and/or Myopia. Six instruments were used for data collection: a questionnaire at the beginning and at the end of the intervention; a Visual Acuity Assessment by the Snellen Optometric Scale, a Field Journal, an Individual Collaborator Record, and also Medical Reports. The protocol consisted of exercises, based on Meir Schneider's Self-Healing method. Results: The results were significant in the increase of visual acuity, as well as in presbyopia, body satisfaction, self-esteem, decreased eye fatigue, detachment of glasses, increased peripheral enlargement, eye attention, memory and the acquisition of knowledge about vision care. Conclusion: It is considered that Ophthalmic Physiotherapy, through the Self-Healing method, is an important tool as an intervention that can recover and/or prevent ocular problems. [resumo fornecido pelo autor]
Physiotherapeutic practices in visual acuity
Introdução: Na Fisioterapia Oftálmica são realizados exercícios para aumentar a função ocular. A Miopia e o Astigmatismo são erros refrativos que causam alteração da visão à distância. Objetivo: objetiva-se neste estudo, verificar a influência da Fisioterapia nas alterações visuais e nas dores e desconfortos musculares. Metodologia: A pesquisa caracteriza-se por um paradigma qualitativo do tipo observacional descritivo, tipo de estudo antes e depois com um grupo de cinco participantes voluntários que apresentavam Astigmatismo e/ou Miopia. Foram utilizados seis instrumentos para coleta de dados: um Questionário no início e no final da intervenção; uma Avaliação da Acuidade Visual pela Escala Optométrica de Snellen, um Diário de Campo, uma Ficha Individual do Colaborador e também Laudos Médicos. O protocolo consistiu em exercícios, baseado no Método Self-Healing de Meir Schneider. Resultados: Os resultados foram significativos no aumento da Acuidade Visual, bem como, na presbiopia, na satisfação com o corpo, na autoestima, na diminuição da fadiga ocular, no desapego do uso dos óculos, no aumento da ampliação periférica, na atenção do olhar, na memória e na aquisição do conhecimento sobre os cuidados com a visão. Conclusão: Considera-se que a Fisioterapia Oftálmica, através do Método Self-Healing, é uma importante ferramenta como intervenção que pode recuperar e/ou prevenir problemas oculares e diminuir dores musculares. [resumo fornecido pelo autor]
Keywords: Acuidade Visual; Fisioterapia; Miopia; Astigmatismo